Microwave Irradiated Solid Phase and Catalyst-free Hantzsch 1,4-dihydropyridine Synthesis: Spectral Characterization, Fluorescence Study, and Molecular Crystal Structure - Maru, Minaxi S.; Kim, Dongwon; Behal, Jagriti; Jung, Ok-sang (Current Chinese Chemistry, 2022)
Background: Solvent- and catalyst-free synthesis of 1,4-dihydropyridines (1,4-DHPs) under microwave radiation is directly dealt with the concept of green chemistry. They are the class of pharmacological agents and drugs used as Ca2+ channel blockers, and they behave as photoelectronic functional materials to exhibit fluorescence activity because of the electron-donating and withdrawing groups present in them.Objective: An efficient and rapid microwave-assisted synthesis of 4-(3-bromo-4-hydroxy-5-methoxyphenyl)-3,5-dicarbmethoxy-2,6-dimethyl-1,4-dihydropyridine (4) has been achieved under solvent- and catalyst-free conditions using three components 3-bromo-4-hydroxy-5-methoxy benzaldehyde, 3-oxobutanoic acid methyl ester, and ammonium carbonate in 25 minutes, which was then subjected to spectroscopic characterization, single-crystal X-ray, and fluorescence study.Methods: The characterization methods were 1H and 13C NMR, FT-IR, LC-MS, and elemental analysis. The single crystal structure was developed using a mixture of Methanol: Tetrahydrofuran and was determined by the single-crystal X-ray diffraction method. The fluorescence study was accomplished in a spectrofluorometer by taking cresyl violet as a reference with two organic solvents, methanol and chloroform.Results: The crystal structure is monoclinic, space group P21/n with a = 11.0557(3) Å, b = 7.3544(2) Å, c = 22.4852(7) Å and β = 104.107(2)°. The used single-crystal size is 0.200 × 0.200 × 0.200 mm3. The NH⋅⋅⋅⋅O type intermolecular hydrogen bond is observed between N(1) and O(2) atoms. The absorption and fluorescence spectra were found to depend on the chemical nature of the substituents available on C(4), C(2), and C(3) atoms of the 1,4-DHP ring and solvent properties.Conclusion: The X-ray study shows flattened boat conformation of the 1,4-DHP ring and the presence of intermolecular hydrogen bonding, a major cause of the Ca2+ channel antagonist. More fluorescence has been shown in methanol than chloroform, and the fluorescence nature of the compound (4) may find potential application in the field of biology and chemical sensor.
Keywords: spectrofluorometer